Estrategias de marketing digital de Distribuidora Touma S.A. DITOSA en la ciudad de Babahoyo del período 2023. - Obando Vera, Emanuel Alfredo (2024)
The study carried out at Distribuidora Touma S.A. DITOSA, located in the city of Babahoyo, sought to deepen the understanding of the deficiencies and opportunities within its digital marketing strategies. In an increasingly competitive market, the need to optimize these strategies becomes a priority to ensure a solid positioning and a lasting competitive advantage. The rationale for this study lay in the preliminary observation that, despite the growing importance of digital marketing, there were significant gaps in the implementation and effectiveness of DITOSA's strategies, potentially limiting its growth and success in the local market. To identify these deficiencies, define more effective digital marketing strategies and evaluate their impact on DITOSA's market positioning, a mixed methodological approach was adopted. This approach combined qualitative and quantitative analysis of data collected through surveys of consumers and marketing personnel.